Microbiological and Chemical Characterization of Different Composts - Dienes, Éva (Acta Agraria Debreceniensis, 2003)
Composting of agricultural waste is considered particularly important from the point-of-view of environmental protection. Degradation of organic substance results in a significant reduction of waste volume. The end product of the composting process, mature compost, can be used as soil coverage against excess loss of wastes, for mulching, for organic manure etc. The problem of composting has come into limelight in environmental studies and in agriculture. The quality of the mature compost is determined by physical, chemical and biological parameters of the composting process which, in turn, depend on initial composition of the raw materials, the technology, e.g. regular mixing and moistening and on environmental factors. Quality is the key question in compost use. We studied the composting process in compost windrows of different raw material composition. We measured temperature, humidity content, pH, organic substance content, nitrogen and carbon content. We counted the number of bacteria, microscopic fungy, ammonifying and cellulose decomposing microorganisms. We directed the composting process with turning weekly (to provide oxygen) and watering (to provide humidity content 40-60%). We set up windrows of 1 m3 volume from dry plant substances (cornstalk, pea straw, tomato stalk and crop, weeds) and cow manure not older than 1 week. The cow manure was used at ratios of 0%, 35%, 50%, 65% and 100%, respectively. We measured changes in compost temperature relationship with outside temperature until they were almoust the same. Humidity was 40-60% in most cases. At the beginning of the process, pH was slightly acidic-neutral; it later becomes neutral-slightly alkaline (pH: 6.93-8.02) as ammonia is liberated from proteins. At the end of the process, pH decreased again, due to humification. Organic substance content decreased as microorganisms mineralized them. Organic carbon content decreased gradually due to microorganisms used it as an energy. Total nitrogen content increased until middle of july and decreased gradually until than. The carbon/nitrogen rate were higher in the beginning, it decreased until july-august and increased by smaller degree until end of the process. The number of bacteria was higher in the first three weeks and between june-september. The number of cellulose degrading bacteria was the highest in the first three month, the number of ammonifying bacteria was the highest from the end of may until sepember. The number of microscopic fungy was significant in the second part of process, after july.